Barriers and facilitators to physical activity and further digital exercise intervention among inactive British adolescents in secondary schools: a qualitative study with physical education teachers - Moore, Richard; Edmondson, Lee; Gregory, Maxine; Griffiths, Kerry; Freeman, Elizabeth (Frontiers in Public Health, 2023)
Background: Research shows that schools’ efforts to improve children and young people’s (CYP) physical activity (PA) behaviours have been unsuccessful. The study investigates Physical Education (PE) teachers’ perceptions of barriers to physical activity (PA) for inactive CYP in secondary schools and to identify facilitators to support future digital public health intervention design, using the COM-B model of behaviour change and Theoretical Domains Framework. Method: This study is a qualitative examination of the perceptions of PE teachers of inactive CYP in deprived secondary schools in England. The method involved structured telephone interviews with 156 Heads of PE in schools and analysed the data with thematic analysis. Results: The study provides a comprehensive understanding of the barriers to PA in secondary schools from the unique perspective of PE teachers. The research identifies 21 barriers to PA and details the main sources of behaviour, intervention functions, policy functions and behaviour change tools that can be applied to support behaviour change for inactive adolescents. The authors suggest the use of digital approaches, particularly conversational AI, to provide a more personalised, natural language experience to engage CYP at scale and overcome barriers to PA. Conclusion: The study is the first to apply the COM-B model, Behaviour Change Wheel, and TDF to understand the habits and behaviours of inactive CYP. The findings of this study have important implications for policy and practice, providing a deeper understanding of the barriers to physical activity and potential solutions to overcome them.